2018
DOI: 10.5539/jsd.v11n4p148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Urban Status of Informal Settlements in Indonesia: A Comparative Analysis of Three Case Studies in North Jakarta

Abstract: Informal settlements have become one of the most important issues facing urban areas in Indonesia. The emergence of informal settlements, called ‘kampungs’, in Jakarta has accompanied the rapid urbanization, and it has become more serious in recent decades. This paper evaluates the urban status of informal settlements in Jakarta. The methods used include a comparative analysis of three case studies in North Jakarta: A. Kampung Bandan; B. Kampung Luar Batang; and C. Kampung Muara Baru. This paper founds that up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 14 publications
1
21
1
1
Order By: Relevance
“…Therefore, streets in Kampung areas are very narrow and mainly suitable for pedestrians or motorcycles (Hidayati, Yamu, & Tan, 2020). In a study of informal settlements in Jakarta, Alzamil (2018) describes the internal roads as "very narrow, winding, and non-paved" in which emergency vehicles cannot commute (Alzamil, 2018). In a similar study, Hidayati et al (2020) have shown that streets with a width of 2 meters or less are an indication of informal settlement (Hidayati et al, 2020) (Figure 6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, streets in Kampung areas are very narrow and mainly suitable for pedestrians or motorcycles (Hidayati, Yamu, & Tan, 2020). In a study of informal settlements in Jakarta, Alzamil (2018) describes the internal roads as "very narrow, winding, and non-paved" in which emergency vehicles cannot commute (Alzamil, 2018). In a similar study, Hidayati et al (2020) have shown that streets with a width of 2 meters or less are an indication of informal settlement (Hidayati et al, 2020) (Figure 6).…”
Section: Methodsmentioning
confidence: 99%
“…Geometric order in the urban fabric refers to the regular and hierarchal street patterns as well as the consistent building placement and block patterns (Rubinowicz, 2000). Conversely, informal settlements are generally described as irregular forms shaped by residents who do not follow any planning process (Alzamil, 2018), with diverse housing patterns comprising different block sizes and shapes (Jones, 2019). Suhartini and Jones (2020), in a study of informal settlements in Indonesia, argue that the outcome of this self-organisation of the space is a disorder or self-made urban order that is organic with a variety of housing sizes and styles within a settlement (Suhartini & Jones, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunian informal tidak mengindahkan adanya kebutuhan masyarakat akan kesehatan, lingkungan, pencahayaan, dan building regulations (Lombard, 2016). Hunian informal juga tidak memperhitungkan kaidah-kaidah standar perencanaan seperti kepadatan bangunan, jaringan jalan, dan ketersediaan fasilitas (Alzamil, 2018). Kurangnya perencanaan menyebabkan kawasan hunian informal menghadapi masalah ketersediaan fasilitas pelayanan, selain itu hunian informal seringkali mengokupansi ruang terbuka untuk menciptakan ruang hunian (Msimang, 2017).…”
Section: Hunian Informal (Informal Settlements) Perkembangan Dan Karakteristiknyaunclassified
“…According to Alzamil (2018), his research founds that upgrading these settlements in urban slum must be in accordance with a comprehensive plan that includes priority improvements.…”
Section: Introductionmentioning
confidence: 99%